2008
DOI: 10.37236/781
|View full text |Cite
|
Sign up to set email alerts
|

On Rainbow Connection

Abstract: An edge-colored graph $G$ is rainbow connected if any two vertices are connected by a path whose edges have distinct colors. The rainbow connection number of a connected graph $G$, denoted $rc(G)$, is the smallest number of colors that are needed in order to make $G$ rainbow connected. In this paper we prove several non-trivial upper bounds for $rc(G)$, as well as determine sufficient conditions that guarantee $rc(G)=2$. Among our results we prove that if $G$ is a connected graph with $n$ vertices and with mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
143
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 174 publications
(163 citation statements)
references
References 7 publications
5
143
0
3
Order By: Relevance
“…Since ⌈ n−1 k ⌉ = ⌈ n k ⌉ if and only if n ≡ 1 (mod k), we instantly have → rvc(D) = ⌈ n k ⌉ − 1 by (4) and (5). To prove the second part, it suffices to show that → srvc(D) ≥ ⌈ n k ⌉ for n sufficiently large, by (4). Suppose that we have a vertex-colouring of D, using at most ⌈ n k ⌉ − 1 colours.…”
Section: Rainbow Connection Of Some Specific Digraphsmentioning
confidence: 94%
“…Since ⌈ n−1 k ⌉ = ⌈ n k ⌉ if and only if n ≡ 1 (mod k), we instantly have → rvc(D) = ⌈ n k ⌉ − 1 by (4) and (5). To prove the second part, it suffices to show that → srvc(D) ≥ ⌈ n k ⌉ for n sufficiently large, by (4). Suppose that we have a vertex-colouring of D, using at most ⌈ n k ⌉ − 1 colours.…”
Section: Rainbow Connection Of Some Specific Digraphsmentioning
confidence: 94%
“…If true, notice that for graphs with a linear minimum degree n, this implies that rc(G) is at most C / . However, the result from [5] does not even guarantee the weaker claim that rc(G) is a constant. This was proved recently by Chakraborty et al in [3].…”
Section: Introductionmentioning
confidence: 95%
“…Caro et al [5] observed that rc(G) can be bounded by a function of (G), the minimum degree of G. They have proved that if (G) ≥ 3 then rc(G) ≤ n where <1 is a constant and n = |V(G)|. They conjecture that = 3 / 4 suffices and prove that <5 / 6 (a solution to this conjecture was recently announced by Zsolt Tuza).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations